Teaching English as a Language not Subject by Employing Formative Assessment (Journal of Education and Educational Development, 2020)
English is a second language (L2) in Sindh, Pakistan. Most of the public sector schools in Sindh teach English as a subject rather than a language. Besides, they do not distinguish between generic pedagogy and distinctive approaches used for teaching English as a first language (L1) and second language (L2). In addition, the erroneous traditional assessment focuses on only writing and reading skills and the listening and speaking skills of L2 remain excluded. There is a great emphasis on summative assessments, which contribute to a qualification; however, formative assessments, which provide timely and continuous appraisal and feedback, remain ignored. Summative assessment employs only paper-and- pencil based test, while the other current means of alternative assessments like self-assessment, peer-assessment, and portfolio assessment have not been incorporated, and explored yet. Teaching English as a subject not as a language, employing summative assessment not formative, depending on paper-and-pencil based test, and not using the alternative modes of assessment are some of the questions this study will deal with. The study under discussion suggests that current approaches employed for teaching English are misplaced as these take a subject teaching approach rather than a language teaching approach. It also argues for the paradigm shift from a product to process approach to assessment by administering modern alternative assessments.